Full-Range Public Health Leadership, Part 2: Qualitative Analysis and Synthesis - Carlton, Erik L.; Holsinger, James W.; Riddell, Martha C.; Bush, Heather (Frontiers in Public Health, 2015)
Public health leadership is an important topic in the era of U. S. health reform, population health innovation, and health system transformation. This study utilized the full-range leadership model in order to examine public health leadership. We sought to understand local public health leadership from the perspective of local health department leaders and those who work with and for them. Public health leadership was explored through interviews and focus groups with directors (n=4) and staff (n=33) from local health departments. Qualitative analytic methods included reflexive journals, code-recode procedures, and member checking, with analysis facilitated by Atlas.ti v.6.0. Qualitative results supported and expanded upon previously reported quantitative findings. Leading by example and providing individual consideration to followers were found to be more important than other leader factors such as intellectual stimulation, inspirational motivation, or idealized attributes of leaders. Having a clear and competent vision of public health, being able to work collaboratively with other community agencies, and addressing the current challenges to public health with creativity and innovation were also important findings. Idealized leadership behaviors and individual consideration should be the focus of student and professional development. Models that incorporate contextual considerations, such as the situational leadership model, should be utilized and instruction in basic interpersonal skills may prove useful. The development of a detailed leadership assessment and development process for public health practitioners is indicated.